The pre-trial detention of child offenders: some evidence from Malaysia - Ahmad, Nadzriah; Hamid, Abdul Ghafur@Khin Maung Sein; Wok, Saodah (Medwell Journals, 2016)
Many child offenders are deprived of their liberty at the pre-trial process for a long period of time. Lengthy detention at this stage is detrimental to the well-being of child offenders because of the trauma they experience while being detained. However, the effectiveness of the current system in preventing child offenders from being detained at the pre-trial process in Malaysia remains an open question because of the high numbers of child offenders being detained at the pre-trial process. The objectives of this study are to examine such issues by highlighting the in. adequacies of the laws governing the pre-trial detention and to analyse whether the current laws are meeting the requirements of international standards. A mixed quantitative and qualitative approach has been adopted to identify the views of 432 child offenders who participated in the study and the opinions from the stakeholders respectively. The findings revealed that there is a compelling need to reform the current laws governing the pre-trial detention in order to reduce the number of child offenders being deprived of their liberty at the pre-trial process.